Detection of peripheral arterial disease in patients with type 2 diabetes mellitus in family medicine clinic - Biljana Lakić; Saša Turajlić; Verica Petrović (Биомедицинска истраживања, 2019)
Introduction: Peripheral arterial disease (PAD) is a progressive, occlusive and atherosclerotic vascular disease and patients with type 2 diabetes mellitus (DM) are at increased risk of developing this disease. The aim of the study was to determine the frequency of PAD in patients with type 2 DM by measuring the ankle-brachial index (ABI) in the family medicine clinic. Methods: The cross-sectional study included the patients with type 2 DM, registered at the Family Medicine Department of Primary Healthcare Center Laktaši. ABI measurement was carried out by means of the "Boso ABI Mess 100 Oscillometer" apparatus while patients were diagnosed with PAD if the ABI value was <0.9 or >1.3. Results: The study included 178 respondents with type 2 DM, aged ?50 years, whereby 90 of them (50.6%) were men. PAD was found in 26 (14.6%) respondents. There was a statistically significant difference in ABI (left/ right leg) between the patients with PAD and the ones without it (0.82/0.84 vs. 1.04/1.05; p<0.01). The average duration of DM was longer in patients with PAD compared to those without PAD (12 vs. 8 years; p = 0.097) and the mean values of HbA1c were the same in both groups (7.7% vs. 7.9%; p = 0.634). There was no statistically significant difference in the frequency of hypertension, dyslipidaemia and obesity between the patients with and without PAD, respectively. Furthermore, the number of smokers among the patients with PAD was significantly higher (p <0.01). Conclusion: In patients with type 2 DM, PAD prevalence was 14.6%. Diabetes lasted a bit longer in patients with PAD, and among them there were significantly more smokers compared to the group without PAD. The Edinburgh Claudication Questionnaire showed positive results in only a third of patients with PAD. Early PAD diagnosis could be established in considerably larger number of patients with type 2 DM by ABI measurement than by the use of the above-mentioned questionnaire.
Keywords: peripheral arterial disease; patient; type 2 diabetes mellitus; ankle-brachial index (ABI)